Mass Transport in Porous Electrodes Studied by Scanning Electrochemical Microscopy: Example of Nanoporous Gold. Issue 12 (26th June 2019) - Haensch, Mareike; Balboa, Luis; Graf, Matthias; Silva Olaya, Alex Ricardo; Weissmüller, Jörg; Wittstock, Gunther
Abstract: Scanning electrochemical microscopy (SECM) approach curves were measured above different samples of nanoporous gold (NPG) using ascorbic acid as an irreversible redox mediator. Under these circumstances, the microelectrode current is informative in terms of the diffusive mass transport inside the network of pores in the sample, because mediator regeneration at NPG is not possible for an irreversible mediator. The reaction–transport problem was solved by finite element simulation for a wide variety of working distances, film thicknesses, and microelectrode geometries. The Bruggeman equation was used to relate transport properties and porosity. The simulation leads to an analytical expression that allows the determination of porosity values corrected by the tortuosity of insulating and conducting materials. The validity of the approach was demonstrated by applying it to NPG samples for which structural parameters can be varied by the particular dealloying protocol. This procedure is potentially applicable for following coarsening processes in porous electrodes and other materials, because the SECM procedure avoids emersion from electrolyte solution for those determinations. Abstract : Approach with caution : Scanning electrochemical microscopy (SECM) is used to study the effect of porosity of nanoporous gold on the mass transport of an irreversible redox mediator. Results agree well with numerical simulation. A new analytical expression is proposed for determination of porosity from SECM approach curves.